International Relations A Self-Study Guide to Theory - Spindler, Manuela (Verlag Barbara Budrich, 2013)
The book is written for active learners - those keen on cutting their own path through the complex and at times hardly comprehensible world of THEORY in International Relations. To aid this process as much as possible, this book employs the didactical and methodical concept of integrating teaching and self-study. The criteria for structured learning about IR theory will be derived from an extensive discussion of the questions and problems of philosophy of science (Part 1). Theory of IR refers to the scientific study of IR and covers all of the following subtopics: the role and status of theory in the academic discipline of IR; the understanding of IR as a science and what a "scientific" theory is; the different assumptions upon which theory building in IR is based; the different types of theoretical constructions and models of explanations found at the heart of particular theories.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Political Science / International Relations; Political science; Electronic books